Benthic marine litter in shallow fishing grounds in the NW Mediterranean Sea. (15th July 2019) - Galimany, E.; Marco-Herrero, E.; Soto, S.; Recasens, L.; Lombarte, A.; Lleonart, J.; Abelló, P.; Ramón, M.
Highlights: Plastic, fabric, processed wood and clinker were the main litter items collected. High abundance of marine litter accumulated in urban populated areas. Marine litter may reach up to 38% of the fisheries catch in shallow grounds. Marine litter should be considered for the economics of fisheries management. Abstract: Fisheries are one of the main economic sectors affected by marine litter, which can damage gear, reduce catch, and require time to repair or clean nets. This study aims to evaluate the type and density of marine litter in two shallow fishing grounds in the NW Mediterranean Sea, both belonging to the Natura 2000 network. Moreover, it quantifies the fraction of marine litter within the total catch to help understand the potential influence of marine litter on fisheries. Two study areas were selected, one in the vicinity of urban populated areas and high navigational traffic and one in a rural site off an agricultural area. The urban area had more benthic marine litter (393 to 198 kg km −2 ) including clinker (residue from coal-burning steamships), fabric, plastics, and processed wood and accounting for up to 38% of the total catch. The rural area had far less marine litter (34–56 kg km −2 ), accounting for only 5% of the total catch. Marine litter may have potential negative effects on fisheries; thus we propose that government credit trading programs could be promoted to help recover litter from fishing catches, to reduce fishing costs and hazards to marine ecosystems.